2012
DOI: 10.1136/jnnp-2012-303169
|View full text |Cite
|
Sign up to set email alerts
|

Reward modulates spatial neglect

Abstract: BackgroundReward has been shown to affect attention in healthy individuals, but there have been no studies addressing whether reward influences attentional impairments in patients with focal brain damage.MethodsUsing two novel variants of a widely-used clinical cancellation task, we assessed whether reward modulated impaired attention in 10 individuals with left neglect secondary to right hemisphere stroke.ResultsReward exposure significantly reduced neglect, as measured by total targets found, left-sided targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 17 publications
(17 reference statements)
5
34
0
1
Order By: Relevance
“…Hemisphere-specific reward learning mechanisms, as substantiated here, may also explain some recent reports of deficits in hemispatial learning and hemispatial reward processing, specifically in patients with unilateral lesions extending into the striatum (Lucas et al, 2013;Malhotra et al, 2013), i.e. such learning deficits could have been caused by disruptions of striatal reward-and reinforcement learning processes.…”
Section: Biased Neural Reinforcement Learning Relates To Spatial Learmentioning
confidence: 63%
See 1 more Smart Citation
“…Hemisphere-specific reward learning mechanisms, as substantiated here, may also explain some recent reports of deficits in hemispatial learning and hemispatial reward processing, specifically in patients with unilateral lesions extending into the striatum (Lucas et al, 2013;Malhotra et al, 2013), i.e. such learning deficits could have been caused by disruptions of striatal reward-and reinforcement learning processes.…”
Section: Biased Neural Reinforcement Learning Relates To Spatial Learmentioning
confidence: 63%
“…ipsilesional) striatum. Similarly, patients with lesions extending into the contralateral striatum were unable to show reward-related reductions of hemispatial neglect (Malhotra et al, 2013). Together these results suggest that hemispheric asymmetries in striatal function may not only subtend orienting biases, but could also be involved in biasing hemispatial learning.…”
Section: Introductionmentioning
confidence: 64%
“…The attentional imbalance in neglect seems to be a consequence of deficits in exogenous attentional orienting, whereas endogenous orienting appears relatively spared, even if slowed (Bartolomeo et al, 2001). Recent studies revealed that rewards associated with left-sided targets could progressively bias visual exploration toward the left hemispace, in patients suffering from left neglect after damage to right frontoparietal attention networks (Lucas et al, 2013;Malhotra et al, 2013). Interestingly, this spatially specific bias seems to occur without conscious awareness of asymmetric rewards contingencies.…”
Section: Reward Effects In Neglect Patientsmentioning
confidence: 99%
“…En un estudio reciente se ha demostrado que la recompensa puede modular la atención en pacientes con HVE (Malhotra, Soto, Li, y Russell, 2012). Estos autores parten de la base que la recompensa ejerce una poderosa influencia sobre la atención.…”
Section: Rehabilitación De La Heminegligencia Visuo-espacialunclassified